A Conceptual Framework of Work Passion and Key Intelligences among Coaches - Paul Yuseung Doh; Minjung Kim; Brent D Oja (Journal of Applied Sports Management, 2024)
This study proposes a conceptual framework that integrates work passion and three key intelligences: cultural intelligence, digital intelligence, and emotional intelligence, to enhance coaching effectiveness and psychological well-being in sport. The framework explores the anticipated antecedents and outcomes of work passion and these intelligences among coaches. The proposed framework contributes theoretically by highlighting the role of work passion and integrative intelligences as foundational elements for innovative work behaviors in sport coaching, which ultimately enhancing both coaching effectiveness and psychological well-being among coaches. This framework also offers practical insights for sport organizations to strategically invest in coaching development, promoting adaptive, tech-savvy, and inclusive coaching strategies that meet the demands of today’s dynamic sport environment.
Keywords: work passion; coaching effectiveness; cultural intelligence; digital intelligence; emotional intelligence